Columned Halls in Ancient Chorasmia. Issue 2 (3rd July 2017) - Minardi, Michele; Betts, Alison V. G.; Khozhaniyazov, Gairatdin
ABSTRACT: Ancient Chorasmia in the period from around the sixth century BC to the second century AD was rich with large fortified sites, many containing monumental architecture. Some of these buildings were large halls, others smaller columned chambers. With particular reference to the site of Akchakhan-kala, this paper discusses the form, development and origins of Chorasmian columned halls.